2020
DOI: 10.3389/fbioe.2020.00296
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of a Novel Hyperthermostable Bifunctional Cellobiohydrolase- Xylanase Enzyme for Synergistic Effect With Commercial Cellulase on Pretreated Wheat Straw Degradation

Abstract: The novel cellobiohydrolase gene ctcel7 was identified from Chaetomium thermophilum, and its recombinant protein CtCel7, a member of glycoside hydrolase family 7, was heterologously expressed in Pichia pastoris and biochemically characterized. Compared with commercial hydrolases, purified CtCel7 exhibited superior bifunctional cellobiohydrolase and xylanase activities against microcrystalline cellulose and xylan, respectively, under optimal conditions of 60 • C and pH 4.0. Moreover, CtCel7 displayed remarkable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 55 publications
4
16
0
Order By: Relevance
“…Most of the GH6 cellulases are optimally active in the acidic range such as Ctcel6 of Chaetomium thermophilum and TlCel6A of Talaromyces leycettanus (Zhou et al 2017 ; Gu et al 2019 ) and also GH7 CBHs of M. thermophila (MtCel7A) and C. thermophilum (CtCel7) (Kadowaki et al 2018 ; Han et al 2020 ). Only one CBH (MoCel6A) of Magnaporthe oryzae has been reported with the pH optima of 9.0 (Takahashi et al 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the GH6 cellulases are optimally active in the acidic range such as Ctcel6 of Chaetomium thermophilum and TlCel6A of Talaromyces leycettanus (Zhou et al 2017 ; Gu et al 2019 ) and also GH7 CBHs of M. thermophila (MtCel7A) and C. thermophilum (CtCel7) (Kadowaki et al 2018 ; Han et al 2020 ). Only one CBH (MoCel6A) of Magnaporthe oryzae has been reported with the pH optima of 9.0 (Takahashi et al 2010 ).…”
Section: Discussionmentioning
confidence: 99%
“…They also resist denaturation by detergents and surfactants, often used to avoid irreversible adsorption of cellulase on the lignocellulosic substrates, and inactivation due to lignin (Rahikainen et al 2013;Shuddhodana et al 2018). Several reports have demonstrated the benefit of using hyperthermostable glycoside hydrolases in the hydrolysis of lignocelluloses compared to less thermostable enzymes (Peng et al 2015;H€ am€ al€ ainen et al 2016;Benedetti et al 2019;Han, Yang, et al 2020). In addition to hyperthermostable glycoside hydrolases found in thermophilic and hyperthermophilic microorganisms (Khare et al 2015;Shuddhodana et al 2018, Suleiman et al 2020) many such enzymes have also been found in metagenomic sources (Mientus et al 2013;Gladden et al 2014;Escuder-Rodr ıguez et al 2018).…”
Section: Process Advantages Of Hyperthermostable Glycoside Hydrolasesmentioning
confidence: 99%
“…It is likely that successful biomass processing will require the activity of more than one enzyme, as discussed for the conversion of lignocellulosic biomass into sugars (Adsul et al 2020). Enzymes suitable for such reactions have already been found in plants (Huang et al 2019), mesophilic microorganisms (Jacomini et al 2020), and thermophiles (Han et al 2020), and have been identified via the metagenomic analysis of relevant microbial consortia, such as those found in biogas facilities (Klippel et al 2019).…”
Section: Self-catalyzed Processing Of Residual Biomassmentioning
confidence: 99%